Hubungan Literasi Digital Dengan Kemampuan Kognitif Menggunakan Model Blended Learning Berbasis Gender : (The Relationship Between Digital Literacy and Cognitive Ability Using a Gender Based Blended Learning) - Meirany Chodijah Amnari Meirany; Suhendar Suhendar; Setiono Setiono (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study is a quasi-experimental study aimed to determine the relationship between digital literacy skills and cognitive abilities using a blended learning model for class XI SMA Negeri 5 Sukabumi City in the 2021/2022 academic year. The research instrument is based on 4 components of digital literacy, namely 1) Internet Searching, 2) Hypertextual Navigation, 3) Content Evaluation, and 4) Knowledge Assembly. Then for the cognitive ability instrument, it refers to the Revised Bloom's Taxonomy in the form of multiple choice questions, with cognitive levels C1-C6 based on indicators of remembering (C1), understanding/understanding (C2), applying (C3), analyzing (C4), evaluating (C5), and create (C6). The results showed that there was no relationship between digital literacy and cognitive ability using gender-based blended learning with a peer correlation value of 0.832 for female and 0.768 for male, indicating a positive relationship with a strong correlation category. Key words: digital literacy, cognitive ability, blended learning, gender Â ABSTRAK Penelitian ini merupakan penelitian kuasi eksperimen bertujuan untuk mengetahui hubungan kemampuan literasi digital dan kemampuan kognitif menggunakan model blended learning kelas XI SMA Negeri 5 Kota Sukabumi tahun ajaran 2021/2022. Instrumen penelitian disusun berdasarkan 4 komponen literasi digital yaitu 1) Internet Searching, 2) Hypertextual Navigation, 3) Content Evaluation, dan 4) Knowledge Assembly. Kemudian untuk instrumen kemampuan kognitif merujuk pada Taksonomi Bloom Revisi berupa soal pilihan ganda, dengan jenjang kognitif C1-C6 berdasarkan indikator mengingat (C1), memahami/mengerti (C2), menerapkan (C3), menganalisis (C4), mengevaluasi (C5), dan menciptakan (C6). Hasil penelitian menunjukkan tidak adanya hubungan antara literasi digital dengan kemampuan kognitif menggunakan blended learning berbasis gender dengan nilai paerson corelation 0,832 untuk jenis kelamin perempuan dan 0,768 untuk laki-laki dengan menunjukan adanya hubungan positif dengan kategori korelasi kuat. Kata kunci: literasi digital, kemampuan kognitif, blended learning, gender